Comprehensive simulation of salinity transport in irrigated watersheds using an updated version of SWAT-MODFLOW. (January 2023) - Bailey, Ryan T.; Hosseini, Pardis
Abstract: Salinity can have major detrimental impacts on soil health, crop yield, and environmental ecosystem services. In this paper we introduce SWAT-MODFLOW-Salt, a version of SWAT-MODFLOW that simulates the fate and transport of major salt ions (SO4 2−, Cl −, CO3 2−, HCO3 −, Ca 2+, Na +, Mg 2+, K + ) in watershed systems, and focus on its development and application to irrigated stream-aquifer systems. The modeling code accounts for water and salt mass storage in soils, aquifer, and streams, and the movement of water and salt mass in surface runoff, soil lateral flow, percolation and recharge, groundwater flow, and groundwater-surface water exchange. The model is applied to a highly managed, irrigated 700 km 2 region of the saline Lower Arkansas River Valley in Colorado, USA. The model is tested against groundwater salt concentrations and in-stream salt mass loadings, and then used to quantify the impact of soil salinity on crop yield. Highlights: We provide a new version of SWAT-MODFLOW that simulates salt ion transport in watershed systems Salt ions are subject to all major hydrologic fluxes and precipitation-dissolution of salt minerals The SWAT-MODFLOW-Salt code is applied to a saline stream-aquifer system in Colorado The model can be used for salinity management scenario analysis